Data structures and algorithms - Aho, Alfred V.; Hopcroft , John E.; Ullman, Jeffrey D. (Reading, Massachusetts : Addision-Wesley Publishing Company, 1983)
The authors' treatment of data structures in Data Structures and Algorithms is unified by an informal notion of "abstract data types," allowing readers to compare different implementations of the same concept. Algorithm design techniques are also stressed and basic algorithm analysis is covered. Most of the programs are written in Pascal.
Chapter 1. Design and analysis of algorithms -- Chapter 2. Basic data types -- Chapter 3. Trees -- Chapter 4. Basic operations on sets -- Chapter 5. Advanced set representation methods -- Chapter 6. Directed graphs -- Chapter 7. Undirected graphs -- Chapter 8. Sorting -- Chapter 9. Algorithm analysis techniques -- Chapter 10. Algorithm design technique -- Chapter 11. Data structures and algorithms for external storage -- Chapter 12. Memory management -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: DATA STRUCTURES (COMPUTING)